2011
DOI: 10.1039/c1cc13568f
|View full text |Cite
|
Sign up to set email alerts
|

TBAI-catalyzed oxidative coupling of aminopyridines with β-keto esters and 1,3-diones—synthesis of imidazo[1,2-a]pyridines

Abstract: TBAI could catalyze the direct oxidative C-N coupling of 2-aminopyridines with β-keto esters and 1,3-diones, which affords imidazo[1,2-a]pyridines as the products. The reaction was realized under metal-free conditions by using tert-butyl hydroperoxide (TBHP) as the oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(65 citation statements)
references
References 18 publications
0
64
0
1
Order By: Relevance
“…[13] Following this work, we reported that a-substituted bacetyl amides could be converted to a-keto amides via oxidative C À C bond cleavage by treatment with CuCl 2 /BF 3 ·OEt 2 /TBHP under an oxygen atmosphere. [14] On the basis of these results, we hoped that the TBHP-based oxidizing systems might be used to turn a-azido-N-phenylacetamides into a-(aminocarbonyl)iminyl radicals under metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Following this work, we reported that a-substituted bacetyl amides could be converted to a-keto amides via oxidative C À C bond cleavage by treatment with CuCl 2 /BF 3 ·OEt 2 /TBHP under an oxygen atmosphere. [14] On the basis of these results, we hoped that the TBHP-based oxidizing systems might be used to turn a-azido-N-phenylacetamides into a-(aminocarbonyl)iminyl radicals under metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous work in the literature [30][31][32] and our own results described above, we proposed a plausible mechanism for the present reactions, which is shown in Scheme 4. Iodide was initially oxidized by TBHP to Na[IO] − , which was further oxidized to a key intermediate hypoiodite Na[IO 2 ] − (A) with one more equivalent of TBHP [33,34].…”
Section: Resultsmentioning
confidence: 88%
“…Further, a similar reaction was reported using tert-butyl hydroperoxide (TBHP) as the terminal oxidant and tetrabutylammonium iodide (TBAI) as a catalyst (Scheme 5) [37,38]. Next, they reduced alkyl imidazo[1,2-a]pyridine-2-caboxylates 1.36 and 1.37 into the corresponding alcohols 1.38 and 1.39, which can be utilized to transform into the anxiolytic drugs saripidem 1.4 and necopidem 1.3, respectively (Scheme 6) [39].…”
Section: Reaction Of 2-aminopyridines With 13-dicarbonyl Compoundsmentioning
confidence: 85%